2017
DOI: 10.4238/gmr16019483
|View full text |Cite
|
Sign up to set email alerts
|

Marker-trait association analysis for agronomic and compositional traits in sainfoin (Onobrychis viciifolia)

Abstract: ABSTRACT. Sainfoin (Onobrychis viciifolia) is a perennial forage legume with great potential for use in sustainable agriculture due to its low input requirements, good drought tolerance, and production of forage rich in polyphenolic compounds, which are beneficial for animal health. However, its distribution and cultivation are limited due to its moderate agronomic performance and a general lack of well adapted, highly yielding cultivars. Faster progress in breeding is imperative, but is often hampered by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…These are necessary to harness the potential benefits of CTs, and for breeding of new varieties with improved agronomic, nutritional, and antiparasitic traits. The European and Asian sainfoin germplasm is very diverse in terms of morphology, anatomy, drought resistance, CT traits, and genetic polymorphism (Hayot Carbonero, 2011;Zarrabian et al, 2013;Malisch et al, 2015Malisch et al, , 2016Mora-Ortiz, 2015;Kempf et al, 2016Kempf et al, , 2017Kölliker et al, 2017). For example, anatomical trait analysis (xylem/phloem ratio, vessel and sieve tube diameters, and phloem width) suggested that large differences exist in water and solute transport mechanisms between accessions, which are important for drought resistance (Zarrabian et al, 2013).…”
Section: Tannin Variation In Germplasm Collections and Potential For mentioning
confidence: 99%
See 1 more Smart Citation
“…These are necessary to harness the potential benefits of CTs, and for breeding of new varieties with improved agronomic, nutritional, and antiparasitic traits. The European and Asian sainfoin germplasm is very diverse in terms of morphology, anatomy, drought resistance, CT traits, and genetic polymorphism (Hayot Carbonero, 2011;Zarrabian et al, 2013;Malisch et al, 2015Malisch et al, , 2016Mora-Ortiz, 2015;Kempf et al, 2016Kempf et al, , 2017Kölliker et al, 2017). For example, anatomical trait analysis (xylem/phloem ratio, vessel and sieve tube diameters, and phloem width) suggested that large differences exist in water and solute transport mechanisms between accessions, which are important for drought resistance (Zarrabian et al, 2013).…”
Section: Tannin Variation In Germplasm Collections and Potential For mentioning
confidence: 99%
“…They were used to study inbreeding and self-fertilization in sainfoin. In a pilot study, one marker locus was identified that could explain up to 12% of the variation in CT composition (i.e., PC/PD ratio; Kempf et al, 2017). We anticipate that the sequence and molecular marker information now available (Kempf et al, 2016; can be used to assist breeding of novel sainfoin cultivars with CT traits that are optimized for animal nutrition and health.…”
Section: Tannin Variation In Germplasm Collections and Potential For mentioning
confidence: 99%
“…Sainfoin has over a 2-meter-long taproot in mature plants, partly responsible for its drought tolerance. The root is quite branched, especially at the bottom and multiples of thin lateral roots constitute the bulk of the root system (Hayot Carbonero, 2011b; Kempf, 2016; Mora-Ortiz and Smith, 2016). Roots have often been measured at more than 2 m and in dry conditions over 3 m. The Sainfoin root systems rival Lucerne for its ability to access water in the lower soil horizons (personal communication, Beat Boller, ETH, 2011)…”
Section: Botanical Description Of Sainfoinmentioning
confidence: 99%
“…A promising strategy to facilitate selection and breeding for drought tolerance is marker-assisted selection (MAS) to identify genetic markers linked to the traits related to drought tolerance. The basic prerequisite for MAS is the availability of markers that are tightly linked to genes or quantitative trait loci (QTLs) which can be used to select for traits that are difficult to measure or dependent on the developmental stage [6,7].…”
Section: Introductionmentioning
confidence: 99%